Neoadjuvant and adjuvant treatment of renal cell carcinoma. Issue 6 (June 2012) - Thillai, Kiruthikah; Allan, Suzanne; Powles, Thomas; Rudman, Sarah; Chowdhury, Simon
Locally advanced renal cell cancers have a significant recurrence rate following radical nephrectomy. Traditional cytotoxic chemotherapy and immunotherapy have failed to demonstrate a benefit in the adjuvant setting. Recent advances in the treatment of metastatic renal cell carcinoma using agents that target VEGF and the mTOR pathways have radically changed the way metastatic renal cell carcinoma is treated. These drugs may be able to reduce the rate of recurrence in high-risk disease, and are now being assessed in the neoadjuvant and adjuvant settings. This review summarizes the evidence for targeted treatment in both the neoadjuvant and adjuvant setting, and its use with cytoreductive nephrectomy.